Reconstructing Narrative Counseling and Its Relevance to Self-meaning among Vocational High School Students - Kristiana, Efi Tri; Purwoko, Budi; Habsy, Bakhrudin All (IKIP Siliwangi, 2025)
This study aims to evaluate recent findings on narrative counseling in helping students reconstruct their sense of self through a Systematic Literature Review (SLR) approach supplemented with content analysis. The study results indicate that narrative counseling is important in transforming negative internal narratives into positive ones, increasing self-confidence, clarifying self-identity, and strengthening self-control and psychological resilience. The conclusions of this study emphasize that narrative counseling is an effective and viable approach to implement in counseling services within vocational high schools. These findings provide conceptual and practical contributions for school counselors in supporting the development of more positive and empowering self-meaning among students.